2015
DOI: 10.1073/pnas.1507803112
|View full text |Cite
|
Sign up to set email alerts
|

Urine excretion strategy for stem cell-generated embryonic kidneys

Abstract: There have been several recent attempts to generate, de novo, a functional whole kidney from stem cells using the organogenic niche or blastocyst complementation methods. However, none of these attempts succeeded in constructing a urinary excretion pathway for the stem cell-generated embryonic kidney. First, we transplanted metanephroi from cloned pig fetuses into gilts; the metanephroi grew to about 3 cm and produced urine, although hydronephrosis eventually was observed because of the lack of an excretion pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(83 citation statements)
references
References 20 publications
3
80
0
Order By: Relevance
“…In this paper we demonstrated than metanephroi vitrification using M22 medium as vitrification solution support the developmental capability of both 15 days-old and 16 days-old metanephroi. However, although we have focused the study solely from the point of the cryobiological effect, it is important to say that some authors have already shown that transplants of fresh kidney precursors are able to filter blood producing urine [33,35] and synthetizing renal hormones [31,32] such as renin and erythropoietin. In the future, it would be interesting demonstrate the same capacities in developed kidneys from vitrified metanephroi.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper we demonstrated than metanephroi vitrification using M22 medium as vitrification solution support the developmental capability of both 15 days-old and 16 days-old metanephroi. However, although we have focused the study solely from the point of the cryobiological effect, it is important to say that some authors have already shown that transplants of fresh kidney precursors are able to filter blood producing urine [33,35] and synthetizing renal hormones [31,32] such as renin and erythropoietin. In the future, it would be interesting demonstrate the same capacities in developed kidneys from vitrified metanephroi.…”
Section: Discussionmentioning
confidence: 99%
“…However, it's known that new renal tissue developed from metanephroi not only provide an excretion function but also an endocrine function, synthesising renal hormones such as renin and erythropoietin [31,32]. Furthermore, if metanephroi are transplanted beside bladders developed from cloacas, and if cloacaldeveloped bladder was connected to the host ureters, new metanephrodeveloped kidney produces and excretes urine through the recipient ureter, avoiding hydronephrosis and allowing the nascent kidney to continue their growth [33]. These findings, together with the scientific capability to produce specific pathogen-free animals [34] suggest than metanephroi transplantation could be a possible solution for kidney need [26,35].…”
Section: Introductionmentioning
confidence: 99%
“…This concept is applicable to cell and tissue transplants between cloned pigs created from identical cells [30,31,32]. Our ultimate goal was to produce two types of animals, individuals that expressed Plum and individuals that expressed mPlum, in a group of cloned pigs sharing a syngenic background.…”
Section: Discussionmentioning
confidence: 99%
“…While such pancreatic progenitor tissue buds could also be formed from differentiated human iPSC derivatives, the size of a mouse as host for further differentiation into pancreatic progenitor tissue is not sufficient to generate tissue grafts for human patients. Pigs could be more suitable interim hosts for this approach, as demonstrated by the development of de novo kidneys of reasonable size from metanephroi transplanted into the omentum of pigs ( [29]; comment in [30]). Potential immune rejection of human tissue buds in pig hosts could be overcome by using genetically immuno-compromised or immune-deficient pigs [31].…”
Section: Attempts To Develop Human Pancreas In Animal Hostsmentioning
confidence: 99%